Λ = n → ∞ lim n 2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n
Enter the number of digits of Λ as your answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Λ = n → ∞ lim n 2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n = n → ∞ lim exp ( n 1 ln ( 2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n ) ) = exp ( n → ∞ lim n ln ( 2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n ) ) = exp ( n → ∞ lim n ln ( 2 0 2 0 2 0 2 1 n ( 1 + 2 0 2 0 − 2 0 2 1 n 2 0 2 1 2 0 2 0 n ) ) ) = exp ( n → ∞ lim n ln ( 2 0 2 0 2 0 2 1 n ) + ln ( 1 + 2 0 2 0 − 2 0 2 1 n 2 0 2 1 2 0 2 0 n ) ) = exp ⎝ ⎛ n → ∞ lim n ln ( 2 0 2 0 2 0 2 1 n ) + n → ∞ lim n ln ( 1 + 2 0 2 0 n 1 ⋅ ( 1 + 2 0 2 0 1 ) 2 0 2 0 n ) ⎠ ⎞ = exp ⎝ ⎛ n → ∞ lim n 2 0 2 1 n ln 2 0 2 0 + n → ∞ lim n ln ( 1 + ( 2 0 2 0 ( 1 + 1 / 2 0 2 0 ) 2 0 2 0 ) n ) ⎠ ⎞ = exp ( 2 0 2 1 ln 2 0 2 0 + ∞ ln ( 1 + 0 ) ) = 2 0 2 0 2 0 2 1
Number of digits of Λ is given by ⌊ lo g 1 0 Λ ⌋ + 1 = ⌊ 2 0 2 1 lo g 1 0 2 0 2 0 ⌋ + 1 = 6 6 8 0 + 1 = 6 6 8 1 .
Nice solution sir.
Log in to reply
Glad that you like it. Upvote my solution if you have not.
We can rewrite the inside part of the root:
2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n = 2 0 2 0 ( 2 0 2 0 + 1 ) n + ( 2 0 2 0 + 1 ) 2 0 2 0 n
For simplicity and easier reading, let a = 2 0 2 0 . By the binomial theorem:
( a + 1 ) a n = i = 0 ∑ a n ( i a n ) a a n − i ⟹ a ( a + 1 ) n + ( a + 1 ) a n = a ( a + 1 ) n + i = 0 ∑ a n ( i a n ) a a n − i = a ( a + 1 ) n [ 1 + i = 0 ∑ a n ( i a n ) a − ( n + i ) ]
We plug this into the root:
Λ = n → ∞ lim n a ( a + 1 ) n ( 1 + i = 0 ∑ a n ( i a n ) a − ( n + i ) ) = n → ∞ lim a ( a + 1 ) n 1 + i = 0 ∑ a n ( i a n ) a − ( n + i )
We take the log (base 10):
lo g Λ = lo g ( n → ∞ lim a ( a + 1 ) n 1 + i = 0 ∑ a n ( i a n ) a − ( n + i ) ) = n → ∞ lim lo g ( a ( a + 1 ) n 1 + i = 0 ∑ a n ( i a n ) a − ( n + i ) ) = ( a + 1 ) lo g a + n → ∞ lim n 1 lo g ( 1 + i = 0 ∑ a n ( i a n ) a − ( n + i ) ) = ( a + 1 ) lo g a + n → ∞ lim n 1 lo g ( 1 + a n 1 i = 0 ∑ a n ( i a n ) a − i ) = ( a + 1 ) lo g a + n → ∞ lim n 1 lo g ( 1 + a n 1 ( 1 + a 1 ) a n ) = ( a + 1 ) lo g a + n → ∞ lim n 1 lo g ( 1 + ( a ( 1 + a 1 ) a ) n ) = ( a + 1 ) lo g a = 2 0 2 1 lo g 2 0 2 0 ⟹ Λ = 2 0 2 0 2 0 2 1
The number of digits is given by ⌊ lo g Λ ⌋ + 1 = 6 6 8 1
Cool method.
Problem Loading...
Note Loading...
Set Loading...
Let ξ ⟹ ξ ⟹ ξ ⟹ ξ = 2 0 2 0 2 0 2 1 n + 2 0 2 1 2 0 2 0 n = 2 0 2 0 2 0 2 1 n ( 1 + 2 0 2 0 2 0 2 1 n 2 0 2 1 2 0 2 0 n ) = 2 0 2 0 2 0 2 1 n [ 1 + ( 2 0 2 0 2 0 2 1 2 0 2 1 2 0 2 0 ) n ] = 2 0 2 0 2 0 2 1 n ( 1 + ϕ n )
where ϕ = 2 0 2 0 2 0 2 1 2 0 2 1 2 0 2 0 < 1
So, Λ = n → ∞ lim ξ n 1 ∴ Λ = n → ∞ lim [ 2 0 2 0 2 0 2 1 n ( 1 + ϕ n ) ] n 1 = 2 0 2 0 2 0 2 1 [ n → ∞ lim ( 1 + ϕ n ) n 1 ] = 2 0 2 0 2 0 2 1 [ n → ∞ lim ( 1 + ϕ n ) ] n 1 = 2 0 2 0 2 0 2 1 ( 1 + n → ∞ lim ϕ n ) n 1 = 2 0 2 0 2 0 2 1 ( 1 + 0 ) n 1 = 2 0 2 0 2 0 2 1
If a decimal number has the form 1 0 k , it has ⌊ k ⌋ + 1 digits. Λ = 2 0 2 0 2 0 2 1 = 1 0 2 0 2 1 lo g 2 0 2 0 ≈ 1 0 6 6 8 0 . 1 1 5
Therefore, Λ has 6 6 8 1 digits.
N.B. Why ϕ < 1 2 0 2 0 2 0 2 1 2 0 2 0 ⋅ 2 0 2 0 2 0 2 0 2 0 2 0 2 0 2 0 ? 2 0 2 1 2 0 2 0 ? 2 0 2 1 2 0 2 0 ? ( 2 0 2 0 2 0 2 1 ) 2 0 2 0 ? ( 1 + 2 0 2 0 1 ) 2 0 2 0
Now, e = x → ∞ lim ( 1 + x 1 ) x > ( 1 + 2 0 2 0 1 ) 2 0 2 0
So, 2 0 2 0 > e > ( 1 + 2 0 2 0 1 ) 2 0 2 0 ⟹ 2 0 2 0 2 0 2 1 > 2 0 2 1 2 0 2 0